Storage conditions, microbial quality, and transport costs of drinking water from alternative sources in a South African municipality - Nhokodi, Tererai; Sithole, Tariro; Mutingwende, Nhamo; Ristvej, Jozef; Tandlich, Roman (Journal of emergency management, 2023)
Makana Local Municipality is located in the Eastern Cape Province of South Africa. The area is water-scarce and has been undergoing aridification in recent years, ie, there has been a 7-year long drought. At the same time, there has been a breakdown in provision of municipal services, such as drinking water, to the population since at least 2008. Mi-crobial water quality has been a result of this, and monitoring has been a challenge. Given the drought and the prob-lems with drinking water delivery, it was necessary to conduct this study to investigate the microbial quality of alterna-tive water resources that the Makana population can use during the municipal water outage. The microbial water quality of alternative sources of drinking water in the Makana Local Municipality was examined using the H2S test kit and enumeration of the fecal coliforms. Storage of the collected water was examined for potential factors influencing the microbial water quality of the alternative sources of drinking water. The costs of the water provision from the most suitable alternative sources of potable water were calculated. There was a general correlation between the H2S test kit results and the fecal coliform concentrations, with the latter values ranging from <0 to 23 ± 7 colony-forming units/100 mL. The bottled water from two retail outlets was provided the best alternative source of potable/drinking water, which is microbially safe, for the Makana population. If the consumption of the drinking water from an alternative source takes place within 24 hours of collection, then the Fairview spring could also be used as a source of drinking water for Maka-na residents. The total cost per 1 L of drinking water from alternative sources was estimated to be from 1.51 to 5.81 ZAR. Therefore, the maximum cost of daily provision of drinking water from alternative sources would account for a maximum of 0.88 percent of the monthly household expenditure in the middle-to-high-income household. However, the daily costs of such provision of drinking water would account for a maximum of 8.11 percent of the monthly household expenditure in the low-income household. Provision of the drinking water from the alternative sources would have a minor impact of the monthly ex-penditure in the middle-to-high-income households. However, it is likely that the low-income households would not be able to sustain their water supply from alternative sources for longer than 24 hours, during a municipal outage in the drinking water supply.